Self-evident shams : metafiction and comedy in three of Flann O'Brien's novels - Yurkoski, Christopher Charles (My University, 1998)
The aim of this thesis is to analyse the connections between comedy and metafiction evident in Flann O’Brien’s At Swim-Two-Birds, The Third Policeman and The Hard Life. The following pages discuss how these novels express, utilize, subvert and explode typical comic discourse within a postmodern paradigm. As works that contain numerous ontological levels that confuse a reader’s sense of reality, that foregound their status as art and that take the subject of writing itself as a theme. At Swim-Two-Birds, The Third Policeman and The Hard Life all explode traditional modes of representation in general, and the conventional comic vision in particular. Throughout my discussion, I describe and apply theories of laughter (namely, the Incongruity, Superiority and Relief theories) to help describe how the humorous aspects of O’Brien’s work disrupt the reading process and the reader’s expectations o f order and comfort. I also interrogate other comic/humour devices within O’Brien’s works — such as puns, which crack language to let words bleed a variety of meanings, and thus reflect how language is implicit in generating multiple levels of fluid reality. My rhetorical pattern for this thesis consists of analysing the way O’Brien handles the mixing of the comic and metafiction from novel to novel — that is, I chart a progession from the more obvious (At Swim-Two-Birds) to the more subtle (The Third Policeman) to the well-hidden but certainly still evident and important (The Hard Life). I show how O’Brien’s subversion of comic discourse creates a vision of a chaotic, plural reality that is both playful and dark.